Experimental study: leveraging active english communication skills through speech training - Sulistiana, Eva; Adianto, Arda (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2024)
In the age of globalization, having a working knowledge of English can be beneficial for santriwati. These students may get the chance to study or preach overseas as they pursue their studies of religious knowledge and impart it to others. However, according to a survey done at Hafshawaty Islamic Boarding School, santriwati's level of English proficiency is still quite poor. A pre-experimental investigation was carried out with 16 santriwati of 90 population total in order to address this using a one-group pre-post-test design. Primary data were gathered through interviews, and English-speaking competencies were assessed both before and after speech treatment. To obtain a summary of all the variables, univariate analysis employing a frequency distribution is used, t-test and paired t-test bivariate analysis to ascertain the impact of one variable on another. The improvement of pronunciation, fluency, and vocabulary mastery indicates that practicing speech can improve one's ability to speak English.